Maxim Violations on "The Lion in Winter" Movie - Anastasia Juwita Ningsih; Ambalegin Ambalegin (Musamus Journal of Language and Literature, 2022)
The purpose of this research was to determine the maxim that violated in the movie â€œThe Lion in Winterâ€. The characters in the movie were chosen as the data source that has a high probability of violating the maxims. This study used Grice (1989) theory to analyse the types of maxim violation. The method in this research applied the descriptive qualitative method from Creswell (2009). Then, the researchers used the non-participatory technique because the researchers did not include in the event. The pragmatic identity from Sudaryanto (2015) was included to analyse the data. In addition, this research found four type of maxim violation from the data source. Those were 7 data in maxim of quantity, 3 data in maxim of quality, 4 data in maxim of relation and 4 data in maxim of manner.